Interplay of takeaway food outlet exposure and income on diet and obesity: a cross-sectional study in UK Biobank. (November 2016) - Burgoine, T; Sarkar, C; Webster, C; Monsivais, P
Abstract: Background: The proliferation of takeaway food outlets has been called a public health problem by Public Health England and the Chief Medical Officer for England. Evidence indicates that the density of takeaway outlets in neighbourhoods can promote unhealthy eating and obesity. But takeaway outlets tend to cluster in deprived areas, and vulnerability to unhealthy food environments might vary across social groups. This study examined the interplay between exposure to takeaway outlets and individual-level socioeconomic position in relation to diet and obesity. Methods: This cross-sectional study included UK Biobank participants based in Greater London (n=51 361) aged 38–72 years with valid height and weight data, food frequency data, and food environment exposures. Food environment exposures were estimated using geographic information systems and food outlet data from UKMap, as counts of outlets by type, within one-mile radius Euclidean (circular) buffers centred on each participant's home address. Our primary exposure was the number of takeaway outlets as a proportion of all food outlets. Participants were jointly classified on the basis of household income (four groups) and quartile of neighbourhood takeaway outlet proportion to create 16 exposure groups. Regression models estimated the odds of frequent processed meat consumption and obesity. We calculated relative excess risk due to interaction (RERI), relative to a single reference group. Participant data were collected during 2005–13 and analysed in 2016. Findings: Both income and takeaway exposure were systematically associated with frequent consumption of processed meat and obesity. In mutually adjusted models, lowest-income participants were more likely than highest-income participants to be obese (odds ratio 1·53, 95% CI 1·38–1·69); and relative to those least exposed, highest takeaway exposure was also associated with obesity (1·76, 1·61–1·91). In additive models, the combination of lowest income and highest takeaway exposure was associated with substantially increased odds of obesity (2·75, 2·33–3·24), with the RERI indicating significant interaction. Results were similar in diet analyses. Interpretation: We have confirmed the findings of earlier work showing independent associations between income, neighbourhood takeaway outlet exposure, and diet and adiposity. Moreover, we provide evidence of the double burden of low income and an unhealthy neighbourhood food environment, resulting in higher rates of unhealthy diet and obesity. Funding: British Heart Foundation, Cancer Research UK, Economic and Social Research Council, Medical Research Council, National Institute for Health Research, and the Wellcome Trust, under the auspices of the UK Clinical Research Collaboration.